Increased Levels of Airway Neutrophils Reduces the Inhibitory Effects of Inhaled Glucocorticosteroids on Allergen-Induced Airway Eosinophils. Issue 1 (3rd February 2002) - Gauvreau, Gail M; Inman, Mark D; Kelly, Margaret; Watson, Richard M; Dorman, Sandra C; O'Byrne, Paul M
Abstract : BACKGROUND: Treatment with inhaled glucocorticosteroids attenuates allergen-induced airway inflammation but is less effective in people with asthma who have noneosinophilic airway inflammation. OBJECTIVE: Studies in which glucocorticosteroid treatment was used before allergen challenges were re-examined to determine whether the efficacy of steroid treatment could be predicted by baseline levels of sputum inflammatory cells. PATIENTS AND METHODS: Twenty-eight nonsmoking subjects with atopic asthma controlled by beta2 -agonists participated in only one of three studies, each carried out with a double-blind, placebo controlled, randomized, crossover design. Subjects were treated with glucocorticosteroids or placebo for six to eight days and then underwent allergen inhalation challenge. Spirometry was measured for 7 h after allergen challenge, and then sputum inflammatory cells were measured. Sputum inflammatory cells were also measured before and after treatment, and 24 h after allergen challenge. The per cent inhibition of the allergen-induced airway responses by glucocorticosteroids was calculated. RESULTS: Inhaled gluticocorticosteroids significantly attenuated the early and late asthmatic responses, and the number of allergen-induced sputum eosinophils (P<0.05). There was a significant negative relationship between the number of sputum neutrophils at baseline, and the per cent inhibition of allergen-induced sputum eosinophils measured at 7 h (r=-0.61, P<0.001) and 24 h (r=-0.73, P<0.0001) after challenge, suggesting that glucocorticosteroids are less effective in attenuating allergen-induced airway inflammation in subjects with high levels of neutrophils. There was no correlation between the number of sputum eosinophils at baseline and the per cent inhibition of allergen-induced responses. CONCLUSIONS: Baseline airway neutrophils, not eosinophils, can be used to predict the efficacy of inhaled steroids on allergen-induced sputum eosinophils.